Podleganie ubezpieczeniu społecznemu w świetle zasad wspólnotowej koordynacji - Woźniak-Ciosk, Marzena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The aim of this article is to cover basic information about regulations based on EU regulations which coordinate the system of social insurance. These regulations were introduced on the 1st May 2004 and they concern people who, apart from having the period of insurance at work in Poland, also have the periods of insurance together with periods of residence in other EU countries. These factors are important because benefits, both retirement as well as pension, depend on them. Using the rules of co-ordination of the social insurance guarantees the good result in case of contest for social benefit by all the employees working on the territory of the European Union. It was necessary to assure people who start working in EU countries that they will not suffer from the lack of retirement or pension. As the result the free migration within the EU would be possible. EU countries should achieve well co-ordinated system of social insurance to avoid the collision of national regulations connected with the rights to benefit of social insurance and paying premiums. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 442-457